2020
DOI: 10.1101/2020.05.18.101261
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Suppression of liquid-liquid phase separation by 1,6-hexanediol partially compromises the 3D genome organization in living cells

Abstract: Liquid-liquid phase separation (LLPS) contributes to the spatial and functional segregation of molecular processes. However, the role played by LLPS in chromatin folding in living cells remains unclear. Here, using stochastic optical reconstruction microscopy (STORM) and Hi-C techniques, we studied the effects of 1,6-hexanediol (1,6-HD)-mediated LLPS modulation on higher-order chromatin organization in living cells. We found that 1,6-HD treatment caused the enlargement of nucleosome nanodomains and their more … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 86 publications
0
8
0
Order By: Relevance
“…S1A). These conditions seem to work well in previous studies, probably owing to the fact that some studies only focused on dissolving specific type of condensate they are interested in without detecting cell variability, or used tumor-derived cell lines (e.g., Hela [ 49 ], K562 [ 50 ]) which show activation of anti-apoptotic pathways [ 52 ]. Despite cell variability, cell size also matters.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…S1A). These conditions seem to work well in previous studies, probably owing to the fact that some studies only focused on dissolving specific type of condensate they are interested in without detecting cell variability, or used tumor-derived cell lines (e.g., Hela [ 49 ], K562 [ 50 ]) which show activation of anti-apoptotic pathways [ 52 ]. Despite cell variability, cell size also matters.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent studies treating cells with high concentration (5% and 10%, respectively) and long time (15 min and 20 min, respectively) of 1,6-HD have reported different results in 3D reorganization [ 49 , 50 ]. One observed moderate 3D reorganization upon treatment [ 49 ] whereas the other observed a global 3D reorganization that short-range interactions decreased and long-range interactions increased [ 50 ], which is consistent with our observation in cells upon 1.5%, long-term (10 min and 30 min) 1,6-HD treatment and opposite to our results in proper condition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The report by Ulianov et al showed that 5% 1,6-HD, which is structurally similar to 2,5-HD, partially compromises 3D genome organization [ 58 ]. Further, 5% and 10% 1,6-HD cause chromatin hyper-condensation, whereas 2.5% 1,6-HD causes nucleosome clustering slightly similar to that in untreated cells [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…These datasets were processed identically to promoter Capture-C reads (except usage of nofill: 0 setting in HiCUP). We used currently unpublished data on topologically associated domain (TAD) boundaries positions in HeLa cells 35 to analyse localization of detected Capture-C interactions relative to TAD boundaries. To assess the expected number of inter-TAD loops we performed simulations, in which we randomly assigned orientation (forward or backward relative to the reference genome) to the set of intra-chromosomal interactions, which we had described (overall 5107 such interactions).…”
Section: Capture-c and In Situ Hi-c Data Processing And Analysismentioning
confidence: 99%